Hubungan Citizen Trust to Government Dengan Kepatuhan Protokol Kesehatan COVID-19 - Furqon, Hafidh; Herani, Ika (Jurnal Psikologi Udayana, 2023)
Abstrak Virus corona telah bermutasi menjadi varian tipe baru yaitu Omicron dengan tingkat penularan yang tinggi. Bahaya varian jenis ini tidak diimbangi dengan peningkatan Kepatuhan Protokol Kesehatan COVID-19 yang telah ditetapkan pemerintah sehingga menyebabkan naiknya kasus positif. Penelitian ini bertujuan untuk mengetahui hubungan antara kepercayaan warga kepada pemerintah dengan kepatuhan terhadap protokol kesehatan COVID-19. Partisipan berjumlah 214 orang yang diambil menggunakan metode kuantitatif non probability sampling dengan pendekatan accidental sampling. Alat ukur untuk penelitian ini menggunakan Citizen Trust in Government Organization Scale dan Skala Kepatuhan menggunakan COVID-19 Prevention Guidelines Scale. Hasil analisis product moment Pearson dapat disimpulkan bahwa terdapat hubungan positif antara Citizen Trust to Government dengan Kepatuhan Protokol Kesehatan COVID-19. Kata kunci: Citizen Trust to Government; COVID-19; kepatuhan; protokol kesehatan Abstract The coronavirus has mutated into a new type variant, namely Omicron with a high transmission rate. The danger of this type of variant is not matched by increased compliance with the COVID-19 health protocol that has been set by the government, causing an increase in positive cases. This study aims to determine the relationship between citizens' trust in the government and compliance with the COVID-19 health protocol. Participants amounted to 214 people who were taken using a quantitative non-probability sampling method with an accidental sampling approach. The measuring instrument in this study used the Citizens Trust Scale in Government Organizations and the Compliance Scale used the COVID-19 Prevention Guidelines Scale. The results of Pearson's product moment analysis can be concluded that there is a positive relationship between citizens' trust to the government and compliance with health protocol COVID-19. Keywords: Citizen Trust to Governmen;, compliance; COVID-19; health protocol